Aetiology-dependent impairment of mitochondrial function in the failing human heart. (25th November 2020) - Borger, J; Scheiber, D; Horn, P; Pesta, D; Boeken, U; Akhyari, P; Lichtenberg, A; Kelm, M; Roden, M; Szendroedi, J; Westenfeld, R
Abstract: Background: Alterations of mitochondrial function have been identified to play a role in Heart Failure (HF) pathophysiology. Oxidative phosphorylation (OXPHOS) capacity of the myocardium was shown to be reduced in the failing heart. Ineffective mitochondrial function promotes formation of reactive oxygen species (ROS) that may affect remodelling in ischemia. Thus far, human mitochondrial function comparing dilated cardiomyopathy (DCM) and ischemic cardiomyopathy (ICM) resembling the main aetiologies of heart failure with reduced ejection fraction (HFrEF) has not been investigated. Purpose: We hypothesised that 1. ROS production is elevated in left ventricular myocardial tissue specimens of ICM patients compared to DCM. 2. Mitochondrial OXPHOS capacity is higher in left ventricular myocardial tissue specimens of DCM compared to ICM patients. Methods: Myocardial tissue was obtained from the left ventricular apex from 63 patients (38 ICM, 25 DCM) with advanced HFrEF requiring implantation of a Left Ventricular Assist Device (LVAD). We performed high-resolution respirometry (HRR, OROBOROS Oxygraph-2k) in saponine-permeabilised myocardial fibres and measured ROS production fluoroscopically via the Amplex Red method. Statistical analysis was conducted using GraphPad Prism 7 and IBM SPSS v26.0. Results: Groups were of comparable age (61.5±1.2 vs. 59.3±2.4 years, p=n.s.), sex (87% vs 85% male, p=n.s.), diabetic status (32% vs 38.4% type 2 diabetes mellitus, p=n.s.), and body mass index (28.1±0.8 vs. 26.3±1.1 kg/m 2, p=n.s.). We detected reduced myocardial mitochondrial OXPHOS capacity in ICM under state 3 conditions by about 15% (68.7±34.0 vs. 80.9±30.5 pmol/(s*mg), p<0.05), after addition of Glutamate by 25% (78.9±38.7 vs. 104.8±41.2 pmol/(s*mg), p<0.01) as well as after Succinate (115.5±65.5 vs. 155±62.0 pmol/(s*mg), p<0.01), uncoupling agent FCCP (114.1±56.8 vs. 150.5±47.3 pmol/(s*mg), p<0.01), and by about 40% after addition of Complex I inhibitor Rotenone (55.5±25.9 vs. 96.9±28.0 pmol/(s*mg), p<0.001). We detected no difference in ROS production between ICM and DCM (0.6±0.05 vs. 0.76±0.08 pmol/(s*ml), p=n.s.). Conclusion: This is the first human study deciphering distinct alterations in mitochondrial function (OXPHOS capacity) in ventricular myocardium of HFrEF patients. Future studies may address how distinct metabolic patterns at the time of implantation may relate to long-term outcome of HFrEF in terms of remodelling and recovery. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): DFG (German Research Foundation)